2022
DOI: 10.3390/ma15248870
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Mechanism Analysis of Graphite Tailings Environment-Friendly Concrete

Abstract: The development of tailings in concrete technology is not only conducive to the realization of the goal of reducing carbon emissions, but also conducive to the inhibition the occurrence of shortages of sand and gravel supplies. In this study, graphite tailings were used to replace sand in the range of 0~100%, and the mechanical mechanism of graphite tailings concrete was examined through compressive and flexural tests. The mechanical experimental results were evaluated and verified based on concrete macroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Hu et al [13] used graphite tailings as a raw material to prepare foamed ceramics through the high-temperature self-foaming method, which is also an economic treatment for graphite tailings. However, this is still not enough to satisfy the large utilization of graphite tailings for recycling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [13] used graphite tailings as a raw material to prepare foamed ceramics through the high-temperature self-foaming method, which is also an economic treatment for graphite tailings. However, this is still not enough to satisfy the large utilization of graphite tailings for recycling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to study the impact of hybrid SF and polyethylene (PE) fiber (PF) on IOT concrete. However, the existing research about IOT concrete mainly focused on f cu , ductility and elastic modulus [36][37][38][39]. Few studies have examined the resistance of hybrid SF and polyethylene (PE) fiber (PF)reinforced IOT concrete to sulfate F-T cycle resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 8 ] used graphite tailings to prepare cement mortar and found that graphite tailings, with the optimal addition amount being 20 wt%, can significantly improve the freeze-resistance of cement mortar. In another study, Duan et al [ 9 ] studied the feasibility of completely replacing a concrete sand aggregate with graphite tailings. Their results showed that the mechanical strength of the concrete samples underwent a parabolic change when there was an increase in the replacement rate, and the best replacement rate was 30%.…”
Section: Introductionmentioning
confidence: 99%